Gun ownership and fear - Benjamin Dowd-Arrow; Terrence D. Hill; Amy M. Burdette (SSM: Population Health, 2019)
Americans can be divided into two groups: those who own guns and those who do not. Although people who own guns and people who do not own guns are often separated along social, cultural, and political lines, it is unclear whether these divisions might extend to population differences in emotional experience. In this paper, we use national cross-sectional data from the 2014 Chapman University Survey on American Fears (n = 1385) to test whether gun owners are more or less afraid than people who do not own guns. We build on previous work by testing two hypotheses with a broad range of fear-related outcomes, including specific phobias and fears associated with being victimized. The symptom perspective argues that gun ownership is a behavioral expression of fear, that gun owners need guns to protect themselves because they are irrational cowards. Although binary logistic regression models provided minimal support for this idea, there was some evidence to suggest that the odds of gun ownership are higher for people who report being afraid of being victimized by a random/mass shooting. The palliative perspective claims that gun ownership mitigates fear, that owning a powerful weapon is somehow soothing to individuals and their families. Ordinary least squares and negative binomial regression models suggest that people who own guns tend to report lower levels of phobias and victimization fears than people who do not own guns. This general pattern is observed across multiple indicators of fear (e.g., of animals, heights, zombies, and muggings), multiple outcome specifications (continuous and count), and with adjustments for age, gender, race/ethnicity, education, household income, marital status, the presence of children, religious identity, religiosity, religious attendance, political orientation, region of residence, and urban residence. Additional longitudinal research is needed to confirm our findings with a wider range of covariates and fear-related outcomes.